Insular neural system controls decision-making in healthy and methamphetamine-treated rats - Hiroyuki Mizoguchi; Kentaro Katahira; Ayumu Inutsuka; Kazuya Fukumoto; Akihiro Nakamura; Tian Wang; Taku Nagai; Jun Sato; Makoto Sawada; Hideki Ohira; Akihiro Yamanaka; Kiyofumi Yamada (2015)
Significance Patients with addiction have a greater tendency to engage in risk-taking behavior. However, the neural substrates responsible for these deficits remain unknown. Here we demonstrated that chronic methamphetamine-treated rats preferred high-risk/high-reward actions and assigned higher value to high returns, indicative of altered decision-making. Pharmacological studies revealed that the insular neural system controls decision-making in both healthy and methamphetamine-treated rats. We further confirmed the role of the insular cortex in decision-making using designer receptor exclusively activated by designer drug technology. Because decision-making is a cognitive process that influences many aspects of daily living and both mental and physical health, the findings of this study have broader implications.